Energy, environmental and economic assessment of electricity savings from the operation of green roofs in urban office buildings of a warm Mediterranean region. (1st December 2017) - Ziogou, Isidoros; Michopoulos, Apostolos; Voulgari, Vasiliki; Zachariadis, Theodoros
Abstract: Green roofs are an important technique to efficiently mitigate adverse environmental impacts of buildings. This study focuses both on energy conservation and sustainability related aspects of two alternative green roof solutions applied to a typical urban office building in representative climatic areas of Cyprus in the Eastern Mediterranean. Simulations regarding the buildings' energy demand were conducted using EnergyPlus software. Based on these results and using an in-house developed algorithm, the primary energy consumption for each alternative solution was computed, assuming variable refrigerant flow air-to-brine heat pump as heating and cooling system, coupled with a calculation of the associated emissions of carbon dioxide, nitrogen oxides and sulphur dioxide. The analysis shows a reduction in primary energy consumption up to 25% in heating and up to 20% in cooling operation, thanks to the use of green roofs, and a corresponding reduction in emissions. The economic viability of the proposed green roof solutions was also examined, taking into consideration both monetary and environmental costs. The results show that the green roof solutions increase the lifetime cost up to 40, 000 €, however they can lead to additional environmental and economic benefits which are hard to quantify.